Fronesis (Φρόνεσις). Discernimento prudenziale e conformità con la Volontà di Dio nella Somma Teologica di San Tommaso d’Aquino (seconda parte) - Mestre, Alberto (Alpha omega, 2022)
The article proposes to show how the virtue of prudence is of utmost importance in human and Christian life, not only because it establishes the means in each virtue, but also because it offers a prudential judgment (discernment) on how to bring one’s will into conformity with that of God. Prudence makes use of past experiences, one’s education, personal reflection, comparison with known alternatives, to tackle new situations. Deliberation, inquiry, foresight, knowledge of the circumstances, caution and precaution, are a group of related virtues that allow us to appreciate the importance of prudence. The potential parts — eubulia (good deliberation), synesis (right judgment), and gnome (sharpness of judgment) — allow for a nuanced exercise of prudence andlead us to strive to conform ourselves with God’s will and to identifyourselves with him.